1989
DOI: 10.1145/63485.63489
|View full text |Cite
|
Sign up to set email alerts
|

Computer hardware performance: production and cost function analyses

Abstract: Based on microeconomics, computer hardware performance is analyzed using two methods. For the cost function analysis, both purchase and lease prices are used. The results show no economies of scale for the mainframes and superminis during the 1981-l 985 period. YOUNG MOO KANGThere has been significant interest in the economic analysis of computer performance because of its direct implications for corlputer resource management [l]. One of the most im:,ortant issues related to this subject has been the degrees o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Studies on economies of scale in software development confirmed the model in Figure 2 with S 1 = S 2 (Banker & Kemerer, 1989;Banker et al, 1984). Prior research on economies of scale effects in IT management demonstrate a counter-intuitive absence of economies of scale due to constant returns to scale for IT, be it increasing or decreasing (Barron, 1992;Kang, 1989;Mendelson, 1987). Extant literature on IT and business productivity differentiates between labor productivity resulting from the simple substitution of labor by IT and the advantages to be gained from fundamental improvements made to managerial practices, business processes, and strategies (Bresnahan, Brynjolfsson, & Hitt, 2002;Brynjolfsson & Hitt, 2003;Davenport & Short, 1990).…”
Section: Economies Of Scale In Business and Itmentioning
confidence: 53%
“…Studies on economies of scale in software development confirmed the model in Figure 2 with S 1 = S 2 (Banker & Kemerer, 1989;Banker et al, 1984). Prior research on economies of scale effects in IT management demonstrate a counter-intuitive absence of economies of scale due to constant returns to scale for IT, be it increasing or decreasing (Barron, 1992;Kang, 1989;Mendelson, 1987). Extant literature on IT and business productivity differentiates between labor productivity resulting from the simple substitution of labor by IT and the advantages to be gained from fundamental improvements made to managerial practices, business processes, and strategies (Bresnahan, Brynjolfsson, & Hitt, 2002;Brynjolfsson & Hitt, 2003;Davenport & Short, 1990).…”
Section: Economies Of Scale In Business and Itmentioning
confidence: 53%
“…Mendelson, in a more rigorous examination of the same data, found that a simple constant returns to scale model, with random noise, explained the data equally well, and was more consistent with the managerial trend in the increased use of smaller, decentralized hardware [107]. A convenient summary table of this research, along with recent results, is available in [79].…”
Section: Introductionmentioning
confidence: 65%
“…To date, extensive research has been conducted on the economics and econometric modeling of mainframes' and minicomputers' characteristics [5,10,11,14,15]. However, research in the economic analysis of workstations is markedly lacking.…”
Section: Hedonic Price Analysis Of Worktation Attributes H Raghav Rmentioning
confidence: 99%
“…For example. Cale et al [5] and Kang's [14] specifications are essentially a log-log fortntilation in which the logarithm of the price is assumed to be a linear function of the independent variables, or the logarithms of (he independent variables, while Ein-dor and Feldmesser's [11] functions are linear or power transformations of the independent variables and price is assumed to be a linear function of the independent variables considered. A difficulty arises here, since all functional representations appear to fit the relevant data well.…”
Section: Model Selectionmentioning
confidence: 99%